2018
DOI: 10.4314/ijest.v4i4.3
|View full text |Cite
|
Sign up to set email alerts
|

Optical properties of alkaline earth borate glasses

Abstract: Borate glasses containing fixed concentrations of heavy metal oxides (MO= ZnO, PbO, TeO2, Bi2O3) and alkaline earth oxides (R= Mg, Ca, Sr, Ba) are prepared by melt quenching technique. The optical band gap values are estimated from the optical absorption spectra using absorption spectrum fitting (ASF) method. The values of electronic polarizability, optical basicity and interaction parameters of the glass were discussed. The increment of refractive index values in each series is attributed to the substitution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(19 citation statements)
references
References 24 publications
0
19
0
Order By: Relevance
“…The decrease in the optical band gap with precursor concentration may be attributed to the increase in grain size and decrease in structural disorder in the films as observed from Urbach energy analysis. In general it was shown that the band gap of all samples is inverted to Urbach energy [70] and the grain size is in respect to equation…”
Section: Opticalmentioning
confidence: 99%
“…The decrease in the optical band gap with precursor concentration may be attributed to the increase in grain size and decrease in structural disorder in the films as observed from Urbach energy analysis. In general it was shown that the band gap of all samples is inverted to Urbach energy [70] and the grain size is in respect to equation…”
Section: Opticalmentioning
confidence: 99%
“…Reflection loss (R L ), dielectric constant (ɛ) of all the glass samples are evaluated from the corresponding refractive index values using the following relations, Metallic or non-metallic nature of any material can be identified by calculating the metallization criterion [59] given by, If R m > V m , the materials are said to be metallic and they are insulators if R m < V m . Here, we can see that all the prepared glass samples show insulating nature.…”
Section: Molar Polarizability Refractive Index and Molar Refractionmentioning
confidence: 99%
“…where is a constant, ℏ is photon energy, and ( ) is the absorption coefficient. Urbach energy (Δ ) values are determined from the slopes of linear regions of the plots ln versus ℏ [43]. Calculated and acquired Δ values are revealed in Figure 7.…”
Section: Urbach Energymentioning
confidence: 99%